Development of an Arduino-based field heat regulator for fruit storage and transportation - Britaña, Hannah Fretchie A.; Ignalig, Marian Claire R.; Natividad, Eshtriel Sunday T.; Cabelita, Brylle F.; Ecle, Erniel Ghrizcer G.; Cane, Jas Felicisimo A. (Institute of Advanced Engineering and Science, 2024)
Fruit spoilage during transportation is a major problem that results in significant economic losses for fruit producers and distributors. One of the primary causes of fruit spoilage is heat buildup inside the storage container during transportation. Hence, this study was done to design and develop an Arduino-based field heat regulator for fruit storage and transportation, regulate field heat in terms of temperature and humidity monitoring; and assess its influence in terms of the skin color, firmness, and bruising of the fruit specimen. After the conduct of the study, it was found that the regulator underwent several iterations during product development and was tried out in an actual transportation procedure. The results revealed that during transportation the product was subjected to fluctuations in temperature and relative humidity, but the storage regulated heat by maintaining desired conditions. Additionally, there was a significant difference found in terms of the fruit's quality parameters when transported using the proposed storage and the traditional method. In conclusion, this storage has the potential to be used in fruit storage facilities, helping reduce post-harvest losses and decrease the chances of fruits being spoiled easily.